Dehydration, rehydration, and exercise in the heat: Rehydration strategies for athletic competition - Galloway, St. D. (Canadian Journal of Applied Physiology, 1999)
The general consensus is that fluid ingestion should match sweat losses during exercise and that the drink should contain CHO and electrolytes to assist water transport in the intestine and to improve palatability. Postexercise rehydration is essential when the strategies adopted before or during exercise have not been effective. The best postexercise rehydration strategy would be to ingest a large volume of a beverage that contains a CHO source and a high sodium content.